Linear Control of a Nonlinear Equipment Mounting Link - Darren Williams; Javad Tagihpour; Hamed Haddad Khodaparast; Shakir Jiffri (Vibration, 2021)
The linear control of a nonlinear response is investigated in this paper, and a nonlinear model of the system is developed and validated. The design of the control system has been constrained based on a suggested application, wherein mass and expense are parameters to be kept to a minimum. Through these restrictions, the array of potential applications for the control system is widened. The structure is envisioned as a robot manipulator link, and the control system utilises piezoelectric elements as both sensors and actuators. A nonlinear response is induced in the structure, and the control system is employed to attenuate these vibrations which would be considered a nuisance in practical applications. The nonlinear model is developed based on Euler–Bernoulli beam theory, where unknown parameters are obtained through optimisation based on a comparison with experimentally obtained data. This updated nonlinear model is then compared with the experimental results as a method of empirical validation. This research offers both a solution to unwanted nonlinear vibrations in a system, where weight and cost are driving design factors, and a method to model the response of a flexible link under conditions which yield a nonlinear response.